2019
DOI: 10.1161/jaha.119.012772
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Comparison of Fractional Flow Reserve Versus Optical Coherence Tomography to Guide Revascularization of Intermediate Coronary Stenoses: One‐Month Results

Abstract: BackgroundFractional flow reserve (FFR) and optical coherence tomography (OCT) may help both in assessment and in percutaneous coronary intervention optimization of angiographically intermediate coronary lesions. We designed a prospective trial comparing the clinical and economic outcomes associated with FFR or OCT in angiographically intermediate coronary lesions.Methods and ResultsThree hundred fifty patients with angiographically intermediate coronary lesions (n=446) were randomized to FFR or OCT guidance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…Probably this advantage is due to the morphological guidance by the OCT in addition to physiological significance. 22 The results of our study give the information that FFR measured with the intracoronary pressure wire alone, may not be a sufficient tool for guiding revascularization in patients admitted with moderate coronary lesions. Probably addition of clinical data like risk factors, especially diabetes mellitus, clinical presentation, left ventricular function, prior PCI/ CABG status, and associated comorbidities along with FFR values are better predictors for the MACE.…”
Section: Discussionmentioning
confidence: 80%
“…Probably this advantage is due to the morphological guidance by the OCT in addition to physiological significance. 22 The results of our study give the information that FFR measured with the intracoronary pressure wire alone, may not be a sufficient tool for guiding revascularization in patients admitted with moderate coronary lesions. Probably addition of clinical data like risk factors, especially diabetes mellitus, clinical presentation, left ventricular function, prior PCI/ CABG status, and associated comorbidities along with FFR values are better predictors for the MACE.…”
Section: Discussionmentioning
confidence: 80%
“…Thus, we performed a novel analysis of the FORZA trial after an extended follow-up time of 24 months, comparing the subgroup of patients in which PCI was originally deferred based on FFR or OCT. So far, we observed that FFR was associated with lower costs and higher medical management rate while OCT reduced the composite endpoint of major adverse cardiac events (MACE) or significant angina at 13-month [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…This is a post‐hoc analysis based on the Fractional Flow Reserve versus Optical Coherence Tomography to Guide RevasculariZAtion of Intermediate Coronary Stenoses (FORZA) study population (NCT01824030) 10 . The FORZA study is an open‐label, prospective, single‐center, randomized trial designed to compare the costs and rate of adverse clinical outcomes in patients randomized to receive FFR versus OCT‐guided PCI on angiographically intermediate coronary lesion (AICL) 10‐12 . A total of 350 patients with stable or stabilized ischemic heart disease and evidence of AICL were enrolled and randomized 1:1 to FFR guidance or OCT guidance.…”
Section: Methodsmentioning
confidence: 99%